2016
DOI: 10.17099/jffiu.79331
|View full text |Cite
|
Sign up to set email alerts
|

Düzce yöresinde münavebeli otlatmanın bazı toprak özellikleri üzerine etkisi

Abstract: Pastures, one of the four important vegetation types in the world, have great potential not only in terms of forage production for animals, but also in terms of biological diversity. Yet, the pressure of continuous and overgrazing on pastures in Turkey affects both vegetation and soil negatively. Overgrazing leads to soil compaction, thus, soil permeability is influenced in a negative way. It is possible to remove these negative influences via amendment methods or reorganizing grazing. In this study, it was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Previous studies have reported that the grazing can increase BD [32] [34] [51] [52], which results in soil compaction, negatively affecting soil water and crop growth. Therefore, the balance of the soil compaction from the grazing and the effects of the compaction on soil water and crop growth is a key aspect of the land management [53].…”
Section: Soil Bulk Density (Bd) and Water Infiltration Rate (Q S )mentioning
confidence: 99%
“…Previous studies have reported that the grazing can increase BD [32] [34] [51] [52], which results in soil compaction, negatively affecting soil water and crop growth. Therefore, the balance of the soil compaction from the grazing and the effects of the compaction on soil water and crop growth is a key aspect of the land management [53].…”
Section: Soil Bulk Density (Bd) and Water Infiltration Rate (Q S )mentioning
confidence: 99%
“…Seksoncu ortasının mevcuduna bakıldığında bu orta 1623 senesinde 350 kişiyken 1664 yılında 531 kişiydi 20 . Seksoncuların sayısı 18. yüzyılın ikinci yarısında 200 kişi civarındaydı 21 . 16. yüzyılın sonlarında seksoncu ortasına günlük kırk altı, sekiz nefer seksoncu bölükbaşısına sekizer, seksoncu kethüdasına ise dört çift fodula veriliyordu.…”
Section: Seksoncu Ortasının Kuruluşu Gelişimi Ve İlgasıunclassified